2022
DOI: 10.3389/fcvm.2022.1026440
|View full text |Cite
|
Sign up to set email alerts
|

Evolving trends in epidemiology and natural history of cardiac amyloidosis: 30-year experience from a tertiary referral center for cardiomyopathies

Abstract: ObjectiveNatural history of cardiac amyloidosis (CA) is poorly understood. We aimed to examine the changing mortality of different types of CA over a 30-year period.Patients and methodsConsecutive patients included in the “Trieste CA Registry” from January 1, 1990 through December 31, 2021 were divided into a historical cohort (diagnosed before 2016) and a contemporary cohort (diagnosed after 2016). Light chain (AL), transthyretin (ATTR) and other forms of CA were defined according to international recommendat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The second phase of the study showed that the prevalence of cardiac amyloidosis was 29% in consecutive adults with echocardiographic findings suggestive of cardiac amyloidosis and LVEF ≥ 50%, while combined echocardiographic red flags usually present good diagnostic accuracy[ 5 ]. Similarly, Porcari et al [ 6 ] examined mortality rates between ATTR and AL cardiac amyloidosis over a 30-year period in Italy and found that incidence and prevalence rates of ATTR and AL cardiac amyloidosis are much higher the last decade compared to the previous ones, but the 2-year survival of ATTR amyloidosis has improved over the years compared to AL cardiac amyloidosis.…”
Section: Epidemiology Of Attr Cardiac Amyloidosismentioning
confidence: 99%
“…The second phase of the study showed that the prevalence of cardiac amyloidosis was 29% in consecutive adults with echocardiographic findings suggestive of cardiac amyloidosis and LVEF ≥ 50%, while combined echocardiographic red flags usually present good diagnostic accuracy[ 5 ]. Similarly, Porcari et al [ 6 ] examined mortality rates between ATTR and AL cardiac amyloidosis over a 30-year period in Italy and found that incidence and prevalence rates of ATTR and AL cardiac amyloidosis are much higher the last decade compared to the previous ones, but the 2-year survival of ATTR amyloidosis has improved over the years compared to AL cardiac amyloidosis.…”
Section: Epidemiology Of Attr Cardiac Amyloidosismentioning
confidence: 99%
“…One of the primary challenges is to achieve an early diagnosis of amyloidosis. Despite significant advancements in the understanding of ATTR-CM, including epidemiology, diagnosis, and treatment [21,26,199,283,284] there remains a substantial number of undiagnosed patients who have been observed by different specialists for several years before receiving the correct diagnosis [285][286][287]. This delay in diagnosis not only hampers timely treatment but also has profound emotional effects on patients [285][286][287].…”
Section: Pre-diagnosis Phasementioning
confidence: 99%
“…Currently, patients with ATTR-CA show a more favorable cardiovascular prognosis than patients with AL-CA, which is associated with therapeutic agents that have been developed in recent years. 22…”
Section: Introductionmentioning
confidence: 99%
“…Currently, patients with ATTR-CA show a more favorable cardiovascular prognosis than patients with AL-CA, which is associated with therapeutic agents that have been developed in recent years. 22 The contemporary approach to the diagnosis and treatment of ATTR-CA involves a sequential process. Clinicians must begin by assessing the likelihood of ATTR-CA, relying on clinical features associated with the cardiac amyloidosis phenotype.…”
Section: Introductionmentioning
confidence: 99%